Changes Land Use in Land Consolidation Area in Seminyak, Kuta - Surya Buana, Anak Agung Putu; Wirawibawa, Ida Bagus Gde; Agusintadewi, Ni Ketut (Journal of A Sustainable Global South, 2021)
Land Consolidation (LC), is the government's solution in land acquisition for development. In addition, LC aims to improve the quality of the environment by rearranging plots of land to be more organized and equipped with environmental infrastructure, as well as land tenure in accordance with land use plans. The location of the land consolidation area in Seminyak Village which is close to the center of government, economy and tourism has implications for land use in the area. The phenomenon of land use that occurs in this region tends to ignore the spatial planning that has been determined by the government. If this condition is left unchecked, there will be more violations of land use that are not in accordance with the spatial allocation, leading to spatial conflicts and clutter in regional spatial planning. This study aims to identify changes in land use in the area of land consolidation in the Seminyak Village and the dominant factors underlying the changes in land use. Qualitative methods are used to identify changes in land use, and these dominant factors. Primary data obtained from observations, direct documentation, and the results of interviews with informants determined by purposive sampling. The results showed that there was a mismatch of land use with the plan for spatial planning in the area designated for settlement and green open space. The dominant factors underlying the changes in land use are law enforcement, then environmental factors, economic factors, and socio-cultural factors. The results of this study can be input for the government in formulating policies relating to planning and controlling the use of space in order to create safe, comfortable and sustainable use of space.   Index Terms — land consolidation, land use, land use change